Legal Formulation Policy on the Privacy Protection of Children and Persons with Disabilities in Indonesia - Nabella Maharani Novanta; Bunga Desyana Pratami (Asian Journal of Law and Humanity, 2022)
The Law of the Republic of Indonesia Number 27 of 2022 Concerning Personal Data Protection contains provisions regarding the privacy data of children and persons with disabilities that are specifically regulated. The rules regarding the protection of personal data are important, especially in light of the rapid development of technology. The existence of Personal Data Protection Law must be motivated by the purpose of law as a tool to integrate and coordinate various interests in society by regulating the protection and limitations of these various interests. This study falls under the category of normative-juridical research, which employs prescriptive methods such as logic and legal reasoning. Using a statutory, philosophical, and conceptual approach, this study will examine the existing privacy regulations for children and persons with disabilities and the principles of protection and ideal rules regarding the privacy of children and persons with disabilities in the future. The results of the study show that there are still weaknesses in the protection of children's and persons with disabilities' data; all data on children and persons with disabilities tends to be at risk of being misused because there is still a legal vacuum regarding technical rules for protecting children's and persons with disabilities' data. Unfortunately, the Personal Data Protection Law does not regulate the "special" process in question. Furthermore, there is no definite age standard regarding the classification of children in the Personal Data Protection Law. The Personal Data Protection Law, which regulates the privacy of children and persons with disabilities, is not in accordance with the theory of legal protection and the theory of legal certainty.